Strategic Change Management for E-Keurani System Adoption: Bridging Structural Barriers and User Commitment in Public Service - Aini, Zahriatul; Sari, Linda; Puspita, Desy; Sukma, Daudy; Rahman, Abdul (Jurnal Samudra Ekonomi dan Bisnis, 2026)
The study analyzes the adoption dynamics and structural barriers of the E-Keurani system at the Aceh Civil Service Agency. Using a qualitative case study approach, data were gathered from six key informants via purposive sampling. Findings reveal that while the technology is sound, adoption remains in a transitional phase hindered by a centralized operator model and the absence of unified standard operating procedures (SOPs). These issues create administrative bottlenecks and adaptation challenges, particularly among senior staff. The study identifies a shift from instructive to persuasive internal marketing as the critical link to reinforce the system’s value. The results imply that public sector digital transformation requires a holistic integration of internal marketing and transformational leadership to evolve simple administrative compliance into a sustainable digital organizational culture.